미세플라스틱의 환경노출을 최소화하기 위한 하･폐수 슬러지 관리방안 - 안준영(Junyeong An); 이병권(Byung Kwon Lee); 전병훈(Byong-Hun Jeon); 지민규(Min-Kyu Ji) (Clean Technology, 27(1), 2021)
Due to the negative impacts of microplastics (MPs) on the ecosystem, the investigation of its occurrence and its treatment from sewage and wastewater treatment plants (WWTPs) have received a lot of attention in the recent years. Most MPs are precipitated and removed with the sludge during the treatment process. Proper sludge management is immensely necessary to avoid MP exposure in the environment. However, the domestic research on this aspect is limited. This study reviews appropriate sludge management approaches to decrease environmental MP exposure. This can be achieved through investigating sludge generation and treatment, regulation laws and government policy trends with an emphasis on WWTPs. The ratio of sludge in sewage treatment plants has been observed to be highest in recycling followed by incineration and landfills. Recycling is the highest in fuel followed by construction materials and composting. For WWTPs, the highest ratio is in recycling followed by fuel and landfills, and recycling is confirmed in the following order: incineration > after composting > after solidification > earthworm breeding. Treatment approaches that can increase the exposure of MPs to the ecosystem are considered to be used in landfills and agricultural fields. However, this method is not appropriate given the insufficient capacity of domestic landfills and the sufficient supply of existing chemical and animal manure fertilizers. Instead, it would be rational in terms of environmental preservation to expand the use of fuel and energy in connection with the new and renewable energy policy, and to actively seek the use of sub-materials for construction materials. In order to secure the basic data for the effectiveness of future planning and revision of related laws, it is required to perform an in-depth investigation of the sludge supply and demand status along with the environmental and economic effects. 미세플라스틱으로 인한 생태환경에 미치는 부정적인 영향들이 보고되면서 이의 발생현황 및 처리효율에 대한 연구가 하·폐수처리장을 중심으로 수행되어 왔다. 처리공정 내의 미세플라스틱은 대부분 슬러지에 침전되어 제거되므로 적절한 관리가 필요하나 이와 관련한 국내 연구는 제한적이다. 본 연구에서는 공공하수처리장 및 공공폐수처리장을 대상으로 슬러지의 발생 및 처리현황과 관련 법률 조사 및 정책 동향 파악을 통해 미세플라스틱의 환경노출을 최소화할 수 있는 적절한 관리방안을 검토하였다. 슬러지 처리방법의 조사·분석 결과, 공공하수처리장 슬러지는 재활용 > 소각 > 매립 등 순으로 비율이 높게 나타났으며 이중 재활용은 연료화 > 건축소재 > 퇴비화 순으로 확인되었다. 공공폐수처리장의 경우는 재활용 > 연료화 > 매립 순으로 비율이 높게 나타났으며, 재활용은 소각 후 > 퇴비화 후 > 고형화 후 > 지렁이 사육 순으로 확인되었다. 미세플라스틱의 생태계 노출을 가중 시킬 수 있는 슬러지 처리방법은 매립 및 농업분야의 이용 용도로 판단되며, 해당 방법은 국내 매립장의 수용 용량 부족 현상과 화학비료 및 가축분뇨 비료 등의 충분한 공급 현황을 고려할 때 그 필요성이 낮아 보인다. 대신 신재생에너지 정책과 연계하여 연료화, 에너지화 이용 방안을 확대하고 이외 건축자재 부원료 등의 활용을 적극적으로 모색하는 것이 지속가능한 환경보전 측면에서 보다 합리적일 것으로 예상된다. 향후 동 계획의 실효성과 관련 법 개정을 위한 주요 기초 자료를 확보하기 위해서는 국내 슬러지 수요-공급 현황과 관리 계획의 환경적 영향 및 경제적 효과 등을 심도 있게 연구하는 과정이 필요할 것으로 판단된다.